Treatment of a Vertical Root Fracture Using Dual-Curing Resin Cement: A Case Report - Nima Moradi Majd; Farshid Akhtari; Solmaz Araghi; Hamed Homayouni (Case Reports in Dentistry)
Introduction. Vertical root fracture (VRF) is one of the most frustrating complications of root canal treatment. The prognosis of the root with VRF is poor therefore tooth extraction and root amputation are usually the only treatment options. However, bonding of the fracture line with adhesive resin cement during the intentional replantation procedure was recently suggested as an alternative to tooth extraction. Methods. A vertically fractured left maxillary incisor was carefully extracted, fracture line was treated with adhesive resin cement, a retrograde cavity was produced and filled with calcium-enriched mixture (CEM) cement, and tooth was replanted. Results. After 12 months the tooth was asymptomatic. The size of periapical radiolucency was noticeably reduced and there was no clinical sign of ankylosis. Conclusion. Using adhesive resin cement to bond the fracture lines extraorally in roots with VRF and intentional replantation of the reconstructed teeth could be considered as an alternative to tooth extraction, especially for anterior teeth.